OPERATIONAL SHIP SPEED OPTIMIZATION USING ENERGY EFFICIENCY APPROACH ON PIONEER PASSENGER SHIP - Kus Rizkytama, Hafizh
The shipping industry also plays a role in producing CO2 gas emissions which have a negative impact on the environment and cause climate change, so it is necessary to measure and limit CO2 gas emissions to ship operations. The International Maritime Organization (IMO) has developed a measurement aimed at reducing ship exhaust emissions, namely the Energy Efficiency Operational Indicator (EEOI). This study aims to determine the optimal ship operating speed point to reduce CO2 gas emissions through the EEOI approach by comparing the actual EEOI formulation of the ship and the Predicted EEOI from the parameters of the shipping environmental conditions. The percentage difference between the two values represents the hull roughness factor and the degradation of ship's engine performance. Optimization is held by combining the EEOI formulation, additional ship resistance, and decreasing the cubic function between speed and power. The result is 12 round voyages on a fixed schedule passenger ship (liner) KM. Sabuk Nusantara 104 obtained the percentage difference in the EEOI values of 4.421%. This value is used as a basis for optimization, by reducing the speed by 0.5 knots to 9.5 knots, CO2 gas emissions decrease by 1.49% but sail time increases by 9.02%, and if the speed is reduced by 1.25 knots it becomes 8.75 knots, CO2 emissions decreased 8.61% and sail time increased by 23.37%. The result after docking the ship on CO2 gas emissions is a decrease in the percentage value of the difference between Predicted and Actual EEOI to only 0.25%. Shipping environmental conditions, hull fouling and machinery degradation, as well as the type and quality of fuel used play an important role in the level of CO2 gas emissions in relation to the rate of fuel consumption but also affect the duration of sailing time. In the technical aspect, the speed reduction to 8.75 knots can be applied to the ship KM. Sabuk Nusantara 104 in the same shipping environment conditions, but in the operational aspect it is necessary to consider the objectives of the shipping program on the 3P (People, Planet, Profit) factor in its implementation.